Helping soldiers heal : how the US Army created a learning mental health care system - Srinivasan, Jayakanth; Ivany, Christopher, 1975- (Culture and politics of health care work., 2021)
"The book describes the transformation of the United States Army's mental healthcare delivery system from 'organized anarchy' into a learning mental healthcare system. It provides a systematic roadmap and templates that other healthcare systems, including non-military ones, can use to guide their own mental healthcare transformation efforts"--